Enhancing Students' Speaking Skills Through Storytelling Methods and Image Media at PAUD Uma Kandung Tambarangan - Feka, Frida (The Future of Education Journal, 2023)
This research was conducted to improve children's speaking skills through the storytelling method and card media. To try to give encouragement in one way so that children "speak" properly and correctly through the storytelling method and the media of pictures. The selection of methods for teaching using image media with an image so that children are interested in learning activities. This research is a type of classroom action research (CAR) in the form of recycling, namely: planning, action or action implementation, observation and reflection. This research was carried out using the storytelling method with media images in developing children's speaking skills. This research was conducted in two cycles with the first cycle having three meetings and the second cycle having two meetings. From the results of the study it was concluded that, the learning activities that had been carried out in cycle I still had many weaknesses that had to be corrected in cycle II regarding the planning and implementation of educators, they had not been able to listen to stories and retell the contents of the story simply as many as 16 children (76%) and 5 children (23.8%) could listen to stories and retell the contents of the story in a simple way. Not being able to answer questions about information or information in a simple way as many as 16 children (76.1%) and 5 children (23.8%) could answer questions about information or information in a simple way. In cycle II, listening to stories and retelling the contents of the stories in a simple way. Developing as expected, 4 children (19.04%) and 17 children (80.95%) developed very well in listening to stories and retelling the contents of the stories in a simple way. whereas in answering questions about simple information or information Developing According to Expectations as many as 4 children (19.04%) and 17 children (80.95%) Developed Very Well in answering questions about simple information or information